2023
DOI: 10.1039/d2sm01183b
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation and competition in the collective drive by motor proteins: mean active force, fluctuations, and self-load

Abstract: We consider the dynamics of a bio-filament under the collective drive of motor proteins. They are attached irreversibly to a substrate and undergo stochastic attachment-detachment with the filament to produce...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
0
0
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29] Cilia-like beating and spiral rotation of overdamped semiflexible filaments at high enough activity were predicted in theoretical studies as observed in earlier motility assay experiments. 17,18,20,24,28,[30][31][32] Recent studies explored the navigation of active elements, including that of active polymers, in complex and crowded environments as well as in traps. [33][34][35][36][37][38][39] Nonetheless, filamentous objects of macroscopic size, including natural examples like millipedes, worms, and snakes and engineered entities such as granular, robotic, or hexbug chains, can exhibit significant inertial effects.…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29] Cilia-like beating and spiral rotation of overdamped semiflexible filaments at high enough activity were predicted in theoretical studies as observed in earlier motility assay experiments. 17,18,20,24,28,[30][31][32] Recent studies explored the navigation of active elements, including that of active polymers, in complex and crowded environments as well as in traps. [33][34][35][36][37][38][39] Nonetheless, filamentous objects of macroscopic size, including natural examples like millipedes, worms, and snakes and engineered entities such as granular, robotic, or hexbug chains, can exhibit significant inertial effects.…”
Section: Introductionmentioning
confidence: 99%